Primary Teachers’ Readiness for Online Professional Development in Local Culture - Thu, Hang Nguyen Thi; Ngoc, Bich Tran; Trinh, Cam Ly; Tran-Thi, Ha- Giang (Edelweiss Applied Science and Technology, 2026)
This study investigates primary school teachers’ readiness for online professional development (PD) in local culture-integrated instruction and examines the predictive roles of instructional competence and perceived implementation barriers. Using a quantitative survey design, data were collected from 235 primary school teachers across urban, rural, and mountainous areas of Vietnam. Descriptive statistics, Pearson correlation, and multiple regression analyses were employed to examine the relationships among the variables. The findings indicate that teachers reported high levels of instructional competence and readiness for online professional development, while perceived barriers were moderate. Correlation analysis revealed a significant positive relationship between instructional competence and readiness. Regression results further showed that instructional competence was a strong and significant predictor of readiness, whereas perceived barriers had no significant independent effect. These findings indicate that teachers’ confidence in implementing local culture-integrated instruction plays a more important role in shaping readiness for professional learning than contextual constraints. The study concludes that competence-oriented and culture-responsive professional development approaches are essential for strengthening culturally grounded teaching practices. Practically, the findings support online professional development as an effective and scalable strategy for enhancing teachers’ capacity to implement local culture-integrated instruction, particularly in diverse and resource-constrained educational settings.